Edukasi Manfaat Teknologi Pada Ibu Hamil Yang Service Exellent di Desa Bangun Rejo Kecamatan Tanjung Morawa Kabupaten Deli Serdang - Amelia Erawaty Siregar; Erin Padilla Siregar; Damayanti S; Sri Rezeki; Marta Armita Silaban; Indri Heni Damanik; Hepriani Girsang (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
In the current era of globalization, technological advances are developing so rapidly. One of these technological advances is information technology (IT) which has penetrated into various fields of human life, to store, analyze. One of the advancements in information technology has penetrated the health sector, such as medicine. Advances in the health sector are developing very rapidly, so that many findings have been obtained with assistance in the areas of hospital organization, treatment, and development research from the health sciences themselves. Information technology-based health services are receiving a lot of attention from the world. Mainly due to promises and opportunities that technology can improve the quality of human life This service aims to provide education to pregnant women to be able to detect problems / danger signs of disease. With 3 x Guidance with a maximum time interval of 2 weeks.